Find expert answers and community-driven knowledge on IDNLearn.com. Discover in-depth and trustworthy answers to all your questions from our experienced community members.
Sagot :
To determine which of the given summations represent the series 11, 17, 23, and 29, we need to evaluate each summation for the specified values of [tex]\( n \)[/tex].
Let's consider each summation one by one:
### 1. [tex]\(\sum_{n=1}^4(5n+6)\)[/tex]
Evaluate the expression [tex]\(5n + 6\)[/tex] for [tex]\(n = 1, 2, 3, \text{and} 4\)[/tex]:
- For [tex]\(n = 1: \qquad 5(1) + 6 = 5 + 6 = 11\)[/tex]
- For [tex]\(n = 2: \qquad 5(2) + 6 = 10 + 6 = 16\)[/tex]
- For [tex]\(n = 3: \qquad 5(3) + 6 = 15 + 6 = 21\)[/tex]
- For [tex]\(n = 4: \qquad 5(4) + 6 = 20 + 6 = 26\)[/tex]
The resulting series is [tex]\(11, 16, 21, 26\)[/tex], which does not match [tex]\(11, 17, 23, 29\)[/tex]. Therefore, this summation does not represent the series.
### 2. [tex]\(\sum_{n=1}^4(6n+5)\)[/tex]
Evaluate the expression [tex]\(6n + 5\)[/tex] for [tex]\(n = 1, 2, 3, \text{and} 4\)[/tex]:
- For [tex]\(n = 1: \qquad 6(1) + 5 = 6 + 5 = 11\)[/tex]
- For [tex]\(n = 2: \qquad 6(2) + 5 = 12 + 5 = 17\)[/tex]
- For [tex]\(n = 3: \qquad 6(3) + 5 = 18 + 5 = 23\)[/tex]
- For [tex]\(n = 4: \qquad 6(4) + 5 = 24 + 5 = 29\)[/tex]
The resulting series is [tex]\(11, 17, 23, 29\)[/tex], which matches the target series. Thus, this summation represents the series.
### 3. [tex]\(\sum_{n=0}^3(6(n+1)+5)\)[/tex]
Evaluate the expression [tex]\(6(n+1) + 5\)[/tex] for [tex]\(n = 0, 1, 2, \text{and} 3\)[/tex]:
- For [tex]\(n = 0: \qquad 6(0+1) + 5 = 6(1) + 5 = 6 + 5 = 11\)[/tex]
- For [tex]\(n = 1: \qquad 6(1+1) + 5 = 6(2) + 5 = 12 + 5 = 17\)[/tex]
- For [tex]\(n = 2: \qquad 6(2+1) + 5 = 6(3) + 5 = 18 + 5 = 23\)[/tex]
- For [tex]\(n = 3: \qquad 6(3+1) + 5 = 6(4) + 5 = 24 + 5 = 29\)[/tex]
The resulting series is [tex]\(11, 17, 23, 29\)[/tex], which matches the target series. Thus, this summation represents the series.
### 4. [tex]\(\sum_{n=0}^3(6(n-1)+5)\)[/tex]
Evaluate the expression [tex]\(6(n-1) + 5\)[/tex] for [tex]\(n = 0, 1, 2, \text{and} 3\)[/tex]:
- For [tex]\(n = 0: \qquad 6(0-1) + 5 = 6(-1) + 5 = -6 + 5 = -1\)[/tex]
- For [tex]\(n = 1: \qquad 6(1-1) + 5 = 6(0) + 5 = 0 + 5 = 5\)[/tex]
- For [tex]\(n = 2: \qquad 6(2-1) + 5 = 6(1) + 5 = 6 + 5 = 11\)[/tex]
- For [tex]\(n = 3: \qquad 6(3-1) + 5 = 6(2) + 5 = 12 + 5 = 17\)[/tex]
The resulting series is [tex]\(-1, 5, 11, 17\)[/tex], which does not match [tex]\(11, 17, 23, 29\)[/tex]. Therefore, this summation does not represent the series.
### Conclusion
The summations that represent the series [tex]\(11, 17, 23, 29\)[/tex] are:
- [tex]\(\sum_{n=1}^4(6n+5)\)[/tex]
- [tex]\(\sum_{n=0}^3(6(n+1)+5)\)[/tex]
Let's consider each summation one by one:
### 1. [tex]\(\sum_{n=1}^4(5n+6)\)[/tex]
Evaluate the expression [tex]\(5n + 6\)[/tex] for [tex]\(n = 1, 2, 3, \text{and} 4\)[/tex]:
- For [tex]\(n = 1: \qquad 5(1) + 6 = 5 + 6 = 11\)[/tex]
- For [tex]\(n = 2: \qquad 5(2) + 6 = 10 + 6 = 16\)[/tex]
- For [tex]\(n = 3: \qquad 5(3) + 6 = 15 + 6 = 21\)[/tex]
- For [tex]\(n = 4: \qquad 5(4) + 6 = 20 + 6 = 26\)[/tex]
The resulting series is [tex]\(11, 16, 21, 26\)[/tex], which does not match [tex]\(11, 17, 23, 29\)[/tex]. Therefore, this summation does not represent the series.
### 2. [tex]\(\sum_{n=1}^4(6n+5)\)[/tex]
Evaluate the expression [tex]\(6n + 5\)[/tex] for [tex]\(n = 1, 2, 3, \text{and} 4\)[/tex]:
- For [tex]\(n = 1: \qquad 6(1) + 5 = 6 + 5 = 11\)[/tex]
- For [tex]\(n = 2: \qquad 6(2) + 5 = 12 + 5 = 17\)[/tex]
- For [tex]\(n = 3: \qquad 6(3) + 5 = 18 + 5 = 23\)[/tex]
- For [tex]\(n = 4: \qquad 6(4) + 5 = 24 + 5 = 29\)[/tex]
The resulting series is [tex]\(11, 17, 23, 29\)[/tex], which matches the target series. Thus, this summation represents the series.
### 3. [tex]\(\sum_{n=0}^3(6(n+1)+5)\)[/tex]
Evaluate the expression [tex]\(6(n+1) + 5\)[/tex] for [tex]\(n = 0, 1, 2, \text{and} 3\)[/tex]:
- For [tex]\(n = 0: \qquad 6(0+1) + 5 = 6(1) + 5 = 6 + 5 = 11\)[/tex]
- For [tex]\(n = 1: \qquad 6(1+1) + 5 = 6(2) + 5 = 12 + 5 = 17\)[/tex]
- For [tex]\(n = 2: \qquad 6(2+1) + 5 = 6(3) + 5 = 18 + 5 = 23\)[/tex]
- For [tex]\(n = 3: \qquad 6(3+1) + 5 = 6(4) + 5 = 24 + 5 = 29\)[/tex]
The resulting series is [tex]\(11, 17, 23, 29\)[/tex], which matches the target series. Thus, this summation represents the series.
### 4. [tex]\(\sum_{n=0}^3(6(n-1)+5)\)[/tex]
Evaluate the expression [tex]\(6(n-1) + 5\)[/tex] for [tex]\(n = 0, 1, 2, \text{and} 3\)[/tex]:
- For [tex]\(n = 0: \qquad 6(0-1) + 5 = 6(-1) + 5 = -6 + 5 = -1\)[/tex]
- For [tex]\(n = 1: \qquad 6(1-1) + 5 = 6(0) + 5 = 0 + 5 = 5\)[/tex]
- For [tex]\(n = 2: \qquad 6(2-1) + 5 = 6(1) + 5 = 6 + 5 = 11\)[/tex]
- For [tex]\(n = 3: \qquad 6(3-1) + 5 = 6(2) + 5 = 12 + 5 = 17\)[/tex]
The resulting series is [tex]\(-1, 5, 11, 17\)[/tex], which does not match [tex]\(11, 17, 23, 29\)[/tex]. Therefore, this summation does not represent the series.
### Conclusion
The summations that represent the series [tex]\(11, 17, 23, 29\)[/tex] are:
- [tex]\(\sum_{n=1}^4(6n+5)\)[/tex]
- [tex]\(\sum_{n=0}^3(6(n+1)+5)\)[/tex]
We appreciate your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. Your search for answers ends at IDNLearn.com. Thanks for visiting, and we look forward to helping you again soon.